Cognizance of Child Sexual Abuse Prevention Education among Teachers of Junior Level Schools in Lahore City, Pakistan - Fatima, Dr. Nabiha (Sociological Research And Innovation, 2026)
The present study aims to uncover the existing knowledge gap regarding the prevention of child sexual abuse by discussing teachers’ viewpoint and their classroom practices. A quantitative method was resorted to analyze social and cultural barriers. Three mainstream schools belonging to a franchise system spread over the province was selected and a sample of 141 junior schoolteachers from the three schools participated. The questionnaire was partitioned into three sections focusing on socio-demographics, factual knowledge, and institutional pedagogies. Teachers, being community leaders, with the trust of both parents and children, possess the capability of transcending structural and cultural barriers through educational practices. The analytical data gathered indicates that there exists a huge knowledge gap of prevention in local socio-cultural context across text, audio, and video. Teachers are not being given regular updates on the safeguarding needs of children through the medium of workshops or training programs. It has been suggested based on the findings of this research that introducing preventive strategies in the junior education curriculum could turn the potential future victims into active beneficiaries. In addition, the teachers suggested these training programs would not only help raise their awareness of this serious issue but would also help in its identification. The very fact that child protection is not talked about in parent-teacher meetings indicates the need for a more effective policy to protect children from the threat of sexual abuse.